(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Pontifical solicitude toward the East: mission and functions of the Dicastery for the Oriental Churches The article analyzes the birth and development of the Dicastery for the Eastern Churches within the Roman Curia, as an instrument and expression of the Roman Pontiff’s care for the Eastern Catholic Churches. The establishment of the dicastery represents the culmination of a centuries-long journey, often marked by challenges and shaped by historical, ecclesiological, and legal transformations. Its functions have progressively evolved, reaching the current structure following the reform of the Roman Curia promoted by Pope Francis with the apostolic constitution Praedicate Evangelium. SOMMARIO: 1. Note introduttive - 2. L’istituzione di un organismo per le Chiese Orientali nella Curia Romana: un accidentato percorso - 3. Il periodo successive al Grande Scisma - 4. LaCongregatio de rebus Graecorum - 5. La Congregatio super negotiis sanctae Fidei et religionis catholicae e la Sacra Congregatio de Propaganda Fide - 6. La Sacra Congregatio de Propaganda Fide pro Negotiis Ritus Orientalis - 7. La Sacra Congregatio pro Ecclesia Orientali - 8. (segue) … e il motu proprio Sancta Dei Ecclesia di Pio XI - 9. La Sacra Congregatio pro Ecclesiis Orientalibus - 10. La Congregazione per le Chiese Orientali - 11. (segue) … e il rescriptum ex audientia del 4 aprile 2006 di Benedetto XVI - 12. Il Dicastero per le Chiese orientali - 13. Considerazioni conclusive.